Relationship focus attention level of performance skill of throwing and receiving some of the skills associated with the tool pillar in gymnastics rhythmic - Abed, Eman (Journal of Physical Education, 2007)
The aim of the study : - Identifying the relationship between concentration of attention and the level of performing throwing and receiving the clup in Rhythmic Gymnastics. The procedures : - Method of Research: The descriptive method. - Subjects: First year female students of the college of physical Education – University Baghdad – Al – Jadria – they were (40) students. Statistical Analysis: Media, standard deviation, simple correlation coefficient. Conclusion: There is a significant relationship between concentration of attention and level of performing throwing and receiving the clup. Recommendations: 1. Developing the concentration of attention through teaching sessions. 2. Making similar studies about other aspects of attention. 3. Increasing the teachers information concerning the aspects of attention through making special training courses.